Vulvar squamous intraepithelial neoplasia epithelial thickness in hairy and non-hairy sites: a single center experience from China - Xiao, Jingjing; Chen, Ziren; Xiao, Yinping; Sui, Long; Wang, Chao; Cong, Qing (Frontiers in Oncology, 2023)
Objective: This study aimed to investigate the optimal depth of vulvar intraepithelial neoplasia (VIN) and involved skin appendages to provide evidence for treatment.The study retrospectively enrolled and analyzed the clinical characteristics of all VINs in the obstetrics and gynecology department of a university hospital from January 1, 2019, to December 30, 2021. The study further explored the thickness of epithelium and skin appendages of 285 women with low-grade VIN (VIN 1) and 285 women with high-grade VIN (VIN 2/3).The study included 1,474 VINs: 1,139 (80%) VIN 1 and 335 (20%) VIN 2/3 cases. The VIN 1 and VIN 2/3 groups showed a significant difference in HPV infection (P<0.01) but not in cytology (P=0.499). The majority (89.90%, 1,325) of the cases occurred in one area of the vulva, whereas 10.11% had multifocal areas. VIN commonly occurred on the posterior fourchette (76.85%), labia majora (11.61%), and labia minora (9.92%). The VIN 2/3 group reported a significantly higher positive rate for concurrent Cervical and Vaginal intraepithelial neoplasia (160 of 285) compared with the VIN 1 group (321 of 953) (P=0.000). The involved epithelial thicknesses in VIN 2/3 and VIN 1 were 0.69±0.44 and 0.49±0.23 mm, respectively, both greater than their noninvolved epithelial thickness (0.31±0.19 and 0.32±0.10 mm, p<0.001 and p<0.001, respectively). In circumstances of appendage involvement, VIN thickness was 1.98±0.64 mm.VIN thickness was generally ≤1 mm for the superficial lesions in non-hairy areas. Lesions extending onto hairy areas were about 3 mm, destroying involved skin appendages.